SCOPE AND QUALITY OF LEGAL PROTECTION AFFORDED TO COMPUTER PROGRAMS AS OBJECT OF INTELLECTUAL PROPERTY (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Computer programs are basic components of the usage of digital technology in all aspects of modern life, so the question arises as to how can current legal rules follow the development of digital technology  i.e. computer programs as well as modalities of its usage. The use of digital technology, especially via creation of computer programs, affects the law, and, consequently, leads to the need for adjusting already established legal mechanisms or for creating new ones for this aspect of legal relations. Since creation and usage of computer programs is basically result of human creative activity (intellectual property), the need arises to position and classify, as well as to define rights, obligations and legal protection of subjects and objects involved in these legal relations. Computer program, in the context of the law of Republic of Serbia, is treated as an object of copyright, while comparative law analyses shows different legal treatments in national laws in the region. Having in mind that computer technology develops far more faster than legal regulation can follow, question arises as to what is current scope and quality of legal protection of computer programs, as object of intellectual property. Defined issues will be analyzed within legal systems of the states in the region – Republic of Serbia, Republic of Croatia, Republic of Montenegro and Bosnia and Herzegovina, as well as in the wider context of the law of the European Union and the process of harmonization of national laws with community law.